Streptomyces humi sp. nov., an actinobacterium isolated from soil of a mangrove forest - Zainal, N.; Ser, H.L.; Yin, Wai Fong; Tee, Kok Keng; Lee, L.H.; Chan, Kok Gan (Kluwer (now part of Springer), 2016)
A novel Streptomyces strain, MUSC 119T, was isolated from a soil collected from a mangrove forest. Cells of MUSC 119T stained Gram-positive and formed light brownish grey aerial mycelium and grayish yellowish brown substrate mycelium on ISP 2 medium. A polyphasic approach was used to determine the taxonomic status of strain MUSC 119T, which shows a range of phylogenetic and chemotaxonomic properties consistent with those of the genus Streptomyces. The cell wall peptidoglycan consisted of ll-diaminopimelic acid. The predominant menaquinones were identified as MK-9(H8), MK-9(H6) and MK-9(H4). The polar lipid profile consisted of phosphatidylinositol, phosphatidylethanolamine, glycolipids, diphosphatidylglycerol and four phospholipids. The predominant cellular fatty acids were anteiso-C15:0, iso-C16:0, and anteiso-C17:0. The cell wall sugars were glucose, mannose, ribose and rhamnose. The phylogenetic analysis based on 16S rRNA gene sequence similarity showed that strain MUSC119T to be closely related to Streptomyces rhizophilus JR-41T (99.0 % sequence similarity), S. panaciradicis 1MR-8T (98.9 %), S. gramineus JR-43T (98.8 %) and S. graminisoli JR-19T (98.7 %). These results suggest that MUSC 119T should be placed within the genus Streptomyces. DNA–DNA relatedness values between MUSC 119T to closely related strains ranged from 14.5 ± 1.3 to 27.5 ± 0.7 %. The G+C content was determined to be 72.6 mol %. The polyphasic study of MUSC 119T showed that this strain represents a novel species, for which the name Streptomyces humi sp. nov. is proposed. The type strain of S. humi is MUSC 119T (=DSM 42174T = MCCC 1K00505T).